Analysis of Factors Influencing the Return of People's Business Credit (KUR) in Taman Sari District, West Jakarta - Setyarini, Theresia Avila Dyah; Hariyanti, Dini; Rustam, Rinaldi (Universitas KH. Abdul Chalim Mojokerto, 2024)
This research was conducted to analyze and study the factors that can influence the return of BNI people's business credit (KUR) in Taman Sari District, West Jakarta. The research method used is descriptive qualitative research with data collection techniques through interviews with 9 informants. Data analysis techniques use data triangulation to reveal the facts of the research objectives. The research results show that the factors that influence KUR returns are financial management which is the main basis for continuity consisting of managing income, expenses, and debt wisely, economic conditions consisting of business growth and opportunities for borrowers to increase income, customer risk perceptions influence take a KUR loan because they have an understanding of business risks and business security which includes physical protection, security and legal compliance. The research recommendation is to build a more in-depth risk assessment model by considering factors such as age, length of business, and gender to provide a more accurate picture of potential credit risk. Develop special programs to support groups that tend to experience difficulties in repayment, such as groups with low levels of education or groups with low income levels. Conduct regular monitoring and evaluation of the implementation of this policy to assess its effectiveness and make changes if necessary.